Comparative efficacy of aloe vera mouthwash and chlorhexidine on periodontal health: A randomized controlled trial - Vangipuram, Swathi (J Clin Exp Dent, 2016)
BACKGROUND: With introduction of many herbal medicines, dentistry has recently evidenced shift of approach for treating many inflammatory oral diseases by using such modalities. Aloe vera is one such product exhibiting multiple benefits and has gained considerable importance in clinical research recently. AIM: To compare the efficacy of Aloevera and Chlorhexidine mouthwash on Periodontal Health. MATERIAL AND METHODS: Thirty days randomized controlled trial was conducted among 390 dental students. The students were randomized into two intervention groups namely Aloe Vera (AV) chlorhexidine group (CHX) and one control (placebo) group. Plaque index and gingival index was recorded for each participant at baseline, 15 days and 30 days. The findings were than statistically analyzed, ANOVA and Post Hoc test were used. RESULTS: There was significant reduction (p<0.05) in the mean scores of all the parameters with Aloe Vera (AV) and chlorhexidine group. Post hoc test showed significant difference (p<0.000) in mean plaque and gingival index scores of aloe Vera and placebo and chlorhexidine and placebo group. No significant difference (p<0.05) was observed between AloeVera and chlorhexidine group. CONCLUSIONS: Being an herbal product AloeVera has shown equal effectiveness as Chlorhexidine. Hence can be used as an alternative product for curing and preventing gingivitis. Key words:Aloe vera, chlorhexidine, dental plaque, gingivitis.